Farmers' perception of the effectiveness of agricultural extension services provided by the ministry of food and agriculture and NGO’s in the Central Region of Ghana - Marshall, Cosmas Kweku Adjetey (University of Cape Coast, 2004)
Since independence in 1957, the government of Ghana has dominated and monopolised the supply of physical infrastructure, credit, research, extension and marketing systems for agriculture. However, escalating budget deficits are compelling the government to consider privatisation or private participation of agricultural extension services. However, with the growth in the participation of a third party such as non-governmental organisations (NGOs) in the supply and financing of extension services in Ghana, there is therefore, the need to conduct a study to determine if the involvement of NGOs has affected farmers' perception about the effectiveness of agricultural extension services in the Central Region. A descriptive survey design was used for the study. Multistage cluster sampling was used to select three districts namely Cape Coast, Abura-Asebu-Kwamankese, and Twifo-Hemang Lower Denkyira Stratified random sampling was then used to select 150 farmers based on operational area, type of service provider and sex. The results showed that there were six NGOs engaged in agricultural extension activities in the study districts of the Central Region. However, through collaboration, the Ministry of Food and Agriculture (MoFA) extension staff provided services to NGO farmers. The most widely used form of interaction between MoFA and NGOs involved in agricultural activities was that of collaboration and this was rated as good. It was found out that over 60% of the farmers interviewed were aware of the existence of most of the 19 basic agriculture technologies studied. Whilst very basic technologies, such as the use of improved varieties, timely weeding and inorganic fertilizers were perceived as good, those for line planting and agro-chemica1 storage were perceived as fair. All the technologies on livestock production were perceived as poor. Type of service provider (MoFA or NGO) did not significantly affect farmers' perception about extension effectiveness. The independent farmers’ demographic variables could only explain up to a maximum of 40% of observed variance for the dependent effectiveness variables. Whilst education was the best predictor for the use of improved varieties and neem storage products, farm size was the best predictor variable for row planting, agro-pesticides, agro-chemical storage and improved maize crib storage. The best predictor variable for all the technologies studied on livestock production was total number (types) of livestock raised. Subsequently, the maximum unique significant contribution made by any best predictor variable was 33.1% for crops and 32.7% for livestock technologies. Sixty percent (61%) of the farmers' interviewed were willing to pay for extension advice. Of this, 54% were willing to pay up to 10% of the cost. The recommendations of this study include; • NGOs should employ their own permanent extension staff for the duration of their time-bound projects. The current practice of NGOs using MoFA extension staff without appropriate emoluments is a disincentive for enhanced performance. • Government should begin to look into the issue of privatisation or private participation of extension services possibly through the contract extension system.
xxxiv,319p:,ill